Peran Integrasi Sistem Traking dan Akurasi Waktu Pengiriman terhadap Target Kepuasan Konsumen - Rizqiani, Shilfia; Iwan Prasetyo (STIE Widya Manggala, 2025)
The purpose of this study is to determine the integration of the tracking system and the accuracy of the delivery time of goods on the satisfaction of JNE Ekspress consumers. 100 JNE Ekspress consumers were sampled in this study. The data collection technique from the population used the probability sampling method with multiple linear regression analysis techniques. From the test results, a significant positive influence was obtained between the tracking system integration variable (X1) and the delivery time accuracy variable (X2) on customer satisfaction (Y). Meanwhile, from the determination test, a value of 0.934 was obtained, meaning that the job satisfaction variable can be explained by the tracking system integration variable (X1) and the delivery time accuracy variable (X2) by 93.4%, while the rest is influenced by other variables.